PELUANG DAN TANTANGAN KONVERSI KOPERASI PEGAWAI NEGERI DARI KONVENSIONAL KE SYARIAH KANTOR KEMENTERIAN AGAMA KABUPATEN SOLOK DENGAN ANALISIS SWOT - Zulhelmi Zulhelmi (IAIN Batusangkar, 2021)
This study aims to describe and analyze the Opportunities and Challenges of Conversion of Civil Servant Cooperatives from Conventional to Sharia at the Office of the Ministry of Religion of Solok Regency with SWOT Analysis. This type of research uses field research (field research) with data collection techniques through interviews and documentation. Based on the results of the study, it was concluded that the opportunity for Conversion of Civil Servant Cooperatives from Conventional to Sharia The Office of the Ministry of Religion of Solok Regency was very large because of the enthusiasm of cooperative members moving from conventional to sharia and supported by policymakers and stakeholders in Solok Regency. The challenge is that there is no member decision as the highest law based on Law no. 25 of 1992 concerning cooperatives and Government Regulation (PP) No. 4 of 1994 concerning Requirements and Procedures for Legalization of the Deed of Establishment in conversion to sharia cooperatives, lack of professional personnel in cooperative management and weakness of understanding due to being accustomed to the conventional system, salaries are deducted Savings and loans and when needed can be facilitated so that they are unwittingly trapped in the system of usury, maysir and gharar which are prohibited in Islam